Retinocytoma Undergoing Retinoblastoma Transformation in an Adult Patient - J. Navaratnam; R. Faber; N. Eide; M. Lund-Iversen; Ø. Garred; F. L. Munier (Case Reports in Ophthalmological Medicine, 2023)
We report a 46-year-old male patient with retinocytoma who presented at the age of 31 asymptomatically. An intraocular retinal mass was incidentally found in his right eye, when he underwent ophthalmological assessment for refractive surgery. This tumor consisted of a calcified sessile basis partially covered by a pedunculated salmon-pink growth. Initially, the tumor was diagnosed as a retinocytoma with clinical suspicion of malignant transformation into retinoblastoma and treated by four sessions of laser photocoagulation. Six and a half years later, the tumor relapsed, and he was treated with a Ruthenium plaque. Following brachytherapy, he had two episodes of right-sided vitreous hemorrhage that spontaneously cleared up, and the remaining finding in the vitreous cavity was interpreted as asteroid hyalosis. He underwent vitrectomy about five years following brachytherapy. The analysis of the vitreous material revealed the presence of inactive vitreous seeds composed of small round blue cells, compatible with a type 2 regression.